Effect of Cd2+ molar concentration in CdxZn(1?x)S thin film by chemical bath deposition technique using alternative sulfur precursor - Nurhafiza K.; Chelvanathan P.; Sobayel K.; Munna F.T.; Abdullah H.; Ibrahim M.A.; Techato K.; Sopian K.; Amin N.; Akhtaruzzaman M. (IOP Publishing Ltd, 2023)
Cadmium sulfide; Deposition; Hall mobility; Hole mobility; II-VI semiconductors; Molar concentration; Morphology; Pollution; Thioureas; Zinc compounds; As-grown films; Chemical bath deposition technique; Chemical-bath deposition; Fabrication process; Raman peak; S thin films; Sulfur precursor; Ternary semiconductors; Thin films